2022
DOI: 10.3389/fpubh.2022.1016937
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of insulin degludec/insulin aspart versus biphasic insulin aspart in Chinese population with type 2 diabetes

Abstract: ObjectiveTo evaluate the long-term cost effectiveness of insulin degludec/insulin aspart (IDegAsp) vs. biphasic insulin aspart 30 (BIAsp 30) for the treatment of people with type 2 diabetes mellitus (T2DM) inadequately managed on basal insulin in China.MethodsThe CORE (the Center for Outcomes Research) Diabetes Model, which has been published and verified, was used to simulate disease progression and calculate the total direct medical costs, life years (LYs) and quality-adjusted life years (QALYs) over 30 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The fluctuation of blood glucose, especially the occurrence of postprandial hyperglycemia, can promote the occurrence of oxidative stress injury and increase the risk of atherosclerosis ( 25 , 26 ). Hypoglycemia is a common adverse reaction during insulin therapy, which can increase the risk of various adverse outcomes such as vascular events and cognitive dysfunction ( 27 , 28 ). The occurrence of nocturnal hypoglycemia can often lead to neurological and cardiovascular damage due to untimely intervention, and in severe cases, it can lead to death ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fluctuation of blood glucose, especially the occurrence of postprandial hyperglycemia, can promote the occurrence of oxidative stress injury and increase the risk of atherosclerosis ( 25 , 26 ). Hypoglycemia is a common adverse reaction during insulin therapy, which can increase the risk of various adverse outcomes such as vascular events and cognitive dysfunction ( 27 , 28 ). The occurrence of nocturnal hypoglycemia can often lead to neurological and cardiovascular damage due to untimely intervention, and in severe cases, it can lead to death ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Luo et al compared biphasic insulin aspart (BIAsp) 30 and IDegAsp strategy and found an incremental benefit of 0.0001 LYs (12.439 for BIAsp 30 versus 12.438 for IDegAsp), a 0.280 QALYs gain (9.522 versus 9.242) over a 30-year period, and an ICER of Chinese Yuan (CNY) 13.886/QALY for the IDegAsp strategy [40].…”
Section: Quality Appraisalmentioning
confidence: 99%